The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1002/1097-0142(19851001)56:7<1534::aid-cncr2820560711>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of second neoplasms following megavoltage radiation for pediatric tumors

Abstract: From 1953 to 1975, 330 children received megavoltage for benign or malignant tumors. Fourteen subsequently developed second neoplasms. The 30-year cumulative incidence of second neoplasms was 9.6%. The incidence of second malignant neoplasms may be lower following megavoltage radiation than following orthovoltage radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…One report (Potish et al, 1985) (Sawitsky et al, 1966), but even if this child is excluded our estimate gives an incidence of 6.7% second malignancies at 7 years. A comparable figure of 9.9% at 9 years was reported in adult Hodgkin's disease (Pedersen-Bjergaard & Larsen, 1982).…”
Section: Discussionmentioning
confidence: 65%
“…One report (Potish et al, 1985) (Sawitsky et al, 1966), but even if this child is excluded our estimate gives an incidence of 6.7% second malignancies at 7 years. A comparable figure of 9.9% at 9 years was reported in adult Hodgkin's disease (Pedersen-Bjergaard & Larsen, 1982).…”
Section: Discussionmentioning
confidence: 65%
“…However, standardised incidence ratios by time periods after FPC diagnosis were not published. One hospital-based study of 330 children treated by radiotherapy observed a cumulative incidence of second cancer of 1.7%, 25 years after FPC (Potish et al, 1985). The standardised incidence ratio is not given, but one can infer from the cumulative incidence that it was probably smaller than 2.…”
Section: Discussionmentioning
confidence: 95%
“…Estimation of the 25 years cumulative incidence of second cancer after childhood cancer varies from 1.7% (Potish et al, 1985) to 12.1% (Tucker et al, 1984).…”
mentioning
confidence: 99%
“…Although a genetic predisposition for cancer and previous chemotherapy may be contributing causes to the development of SNs, 5 various reports have highlighted the significant contribution of radiotherapy to the development of SNs in childhood cancer survivors. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18] A radiation dose-effect relationship has been noted for some SNs such as bone sarcomas. 15 Children are particularly susceptible to the carcinogenic effects of radiation, possibly due to the increased rapidity of cell division in various tissues associated with the normal growth and development process.…”
mentioning
confidence: 80%
“…Earlier reports from the University of Minnesota have analyzed the incidence and nature of SNs in a cohort of children who received megavoltage radiation after 1954. 9,19 The current report updates these original studies, but with increased numbers of children in the cohort and a longer follow-up time.…”
mentioning
confidence: 99%